FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN MEMBAYAR PAJAK ORANG PRIBADI YANG BERWIRAUSAHA DENGAN LINGKUNGAN DAN PREFERENSI RISIKO SEBAGAI VARIABEL MODERASI (Studi Empiris pada Wajib Pajak Orang Pribadi yang Berwirausaha Terdaftar di KPP Pratama Bangkinang) - Vavia Yunasih; Emrinaldi Nur DP; Rofika ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The reseach was conducted with a purpose of analyzing the direct effect that directly influence adherence to pay tax, which are motivation, level of education and perception of personal financial situation on the private enterpreneurship with the environment and risk preferences as the moderating variabel.This research was done in the Primary Tax Office Bangkinang with 100 respondents. The collecting sample method used was convenience sampling.The analyticalmethods that was used in this research is helped by of sofware Smart PLS. The result was concluded that the motivation, level of education and perception of personal financial situation have a direct impact on compliance of paying taxes. Environment variable moderated the relationship between motivation, level ofeducation and perception of personal financial situation with adherence to pay taxes and risk preference moderated the relationship between motivation and level of education with adherence to pay taxes. Nontheless risk preference did notinfluence the relationship between perception of personal financial situation with adherence to pay taxes.Keywords: adherence to pay taxes, motivation, perception of personal financial situation, environment and risk preference.